2012
DOI: 10.1248/bpb.b12-00445
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine Prevents Bone Loss in Sciatic-Neurectomized Mice and Inhibits Receptor Activator of Nuclear Factor κB Ligand-Induced Osteoclast Differentiation

Abstract: One of the mediators of osteoclast differentiation is receptor activator of nuclear factor κB ligand (RANKL), which is produced by osteoblasts. Binding of RANKL to its receptor, RANK, activates several signaling pathways, including those involving mitogen-activated protein kinases (MAPKs), nuclear factor κB (NF-κB), nuclear factor of activated T cells c1 (NFATc1) and Ca 2 -calcineurin. In the present study, we found that tetrandrine, a bisbenzylisoquinoline alkaloid extracted from the root of Stephania tetrand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…In this study, we found that fangchinoline suppressed RANKL-induced osteoclast formation and function, and ameliorated bone loss in OVX mice. Our results are in line with previous report which showed that tetrandrine, an analogue of fangchinoline, suppressed RANKLinduced osteoclast differentiation and bone loss in sciatic-neurectomized mice (8).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we found that fangchinoline suppressed RANKL-induced osteoclast formation and function, and ameliorated bone loss in OVX mice. Our results are in line with previous report which showed that tetrandrine, an analogue of fangchinoline, suppressed RANKLinduced osteoclast differentiation and bone loss in sciatic-neurectomized mice (8).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, bone histomorphometry results revealed that the protective effects of fanchinoline is through inhibiting the osteoclasts activity by the relative parameter such as osteoclast number/ bone surface (N.Oc/BS) and osteoclast surface/ bone surface (Oc.S/BS). Our results are in line with recent findings showing an inhibitory effect of tetrandrine on bone loss (8,33), and also provide new mechanistic insights of fangchinoline. In conclusion, fangchinoline attenuated osteoclast formation, function and ameliorated OVX-induced osteoporosis in mice mainly through suppressing RANKL signalling pathways and osteoclast marker genes expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous pharmacological and clinical studies have shown that tetrandrine possesses antiinflammatory, anti-proliferative, immunosuppressive, and antitumor activities (Dong et al, 1997;Lai et al, 1998;Xie et al, 2002;Yoo et al, 2002;Lee et al, 2002;Kuo and Lin, 2003;Wang et al, 2004). In recent years, it was discovered that tetrandrine can inhibit proliferation of human Tenon's capsule fibroblasts and differentiation of osteoclasts (Takahashi et al, 2012;Li et al, 2012). In our previous studies, we showed that tetrandrine inhibited proliferation of HSFs and synthesis of collagen and DNA (Liu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, important issues still require resolution, including the antiadipogenic effect of tetrandrine on obese animal models. Tetrandrine (0.6, 2.0 or 6.0 mg/kg) prevented bone loss in sciatic-neurectomized mice by inhibiting receptor activation of NF-jB ligand-induced osteoclast differentiation (Takahashi et al 2012). We believe that further work will be required to clarify that tetrandrine acts on the expression and/or function of transcription factors which form complexes with the nuclear factor of activated T cells c1 (NFATc1) in osteoclasts.…”
Section: Miscellaneous Usesmentioning
confidence: 99%